Freedom of religion, secularism, and human rights - Bhuta, Nehal (The collected courses of the Academy of European Law, 2019)
This interdisciplinary volume examines the relationship between secularism, freedom of religion and human rights in legal, theoretical, historical and political perspective. It brings together chapters from leading scholars of human rights, law and religion, political theory, religious studies and history, and provides insights into the state of the debate about the relationship between these concepts. Comparative in orientation, its chapters draw on constitutional and political discourses and experience not only from Western Europe and the United States, but also from India, the Arab world, and Malaysia